2011
DOI: 10.1021/nn203669r
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Disorder in Single-Enzyme Experiments: Facts and Artifacts

Abstract: Using a single molecule fluorescence approach, the time series of catalytic events of an enzymatic reaction can be monitored yielding a sequence of fluorescent "on"- and "off"-states. An accurate on/off-assignment is complicated by the intrinsic and extrinsic noise in every single molecule fluorescence experiment. Using simulated data, the performance of the most widely employed binning and thresholding approach was systematically compared to change point analysis. It is shown that the underlying on- and off-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 30 publications
4
84
0
Order By: Relevance
“…37 Recently, it was shown that the existence of dynamic disorder of single enzymatic turnover reactions depends on how one assigns the ON/OFF levels and the most widely used binning and thresholding approach may yield a misleading interpretation. 38 Because some subsequences involving one step transitions in the ON/OFF time series were removed from the analyses, 16 it is desired to confirm how such removals would affect in the analyses based on change point detection method. 36,38 It should also be noted that the SSN scheme groups a set of past subsequences (into a single state) whose transition probability distributions are regarded as identical within an error tolerance determined by the significance level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Recently, it was shown that the existence of dynamic disorder of single enzymatic turnover reactions depends on how one assigns the ON/OFF levels and the most widely used binning and thresholding approach may yield a misleading interpretation. 38 Because some subsequences involving one step transitions in the ON/OFF time series were removed from the analyses, 16 it is desired to confirm how such removals would affect in the analyses based on change point detection method. 36,38 It should also be noted that the SSN scheme groups a set of past subsequences (into a single state) whose transition probability distributions are regarded as identical within an error tolerance determined by the significance level.…”
Section: Discussionmentioning
confidence: 99%
“…38 Because some subsequences involving one step transitions in the ON/OFF time series were removed from the analyses, 16 it is desired to confirm how such removals would affect in the analyses based on change point detection method. 36,38 It should also be noted that the SSN scheme groups a set of past subsequences (into a single state) whose transition probability distributions are regarded as identical within an error tolerance determined by the significance level. The grouping and resultant states depend on this significance level and even if two past subsequences are grouped into a certain state for a specific significance level, it might not be the case for another significance level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is called dynamic disorder [120][121][122][123]. Single molecule experiments have shown that the stochastic waiting time of an enzymatic reaction exhibits a distribution of an exponential rise followed by an exponential decay [124,125]. For a single molecule with slowly interconverting conformational states with different k cat and K m , it follows that…”
Section: New Developments In Enzyme Inhibitionmentioning
confidence: 99%
“…More recent advances in single-molecule techniques are bringing attention to the disordered decay 7 of structural correlations in biomolecules during electron transfer reactions 8 and enzyme catalyzed reactions. [9][10][11][12] Experimental techniques have also inspired new theoretical approaches to disora) jason.green@umb.edu dered kinetics [13][14][15] in the forced unfolding 16,17 and spontaneous folding 18,19 of biomolecules. Disordered kinetics is also of interest in the charge transfer through molecular assemblies because of their potential use in molecular electronics, solar cells, and artificial photosynthesis.…”
mentioning
confidence: 99%